On ethnography - Daynes, Sarah; Williams, Terry M. (Terry Moses) 1948- (Cambridge, United Kingdom Polity, 2018)
"In turn creative thinker and street flaneur, careful planner and adventurer, empathic listener and distant voyeur, recluse writer and active participant: the ethnographer is a multifaceted researcher of social worlds and social life. In this book, sociologists Sarah Daynes and Terry Williams team up to explore the art of ethnographic research and the many complex decisions it requires. Using their extensive fieldwork experience in the United States and Europe, and hours spent in the classroom training new ethnographers, they illustrate, discuss, and reflect on the key skills and tools required for successful research, including research design, entry and exit, participant observation, fieldnotes, ethics, and writing up. Covering both the theoretical foundations and practical realities of ethnography, this highly readable and entertaining book will be invaluable to students in sociology and other disciplines in which ethnography has become a core qualitative research method"--Provided by publisher.
Chapter 1. Foundations of ethnographic fieldwork -- Chapter 2. Thinking about it -- Chapter 3. Getting involved -- Chapter 4. Being there -- Chapter 5. Seeing, Writing, Narrating : Field Notes -- Chapter 6. Writing about it References.
Includes bibliographical references (pages 183-190) and index.
Keywords: Ethnology -- Research -- Methodology